Modelling Stage-discharge Relationships for Hydrological Stations in the Da River Basin using First-kind Chebyshev Polynomial Approximation - Duc Hanh, Nguyen; Tien Giang, Nguyen; Tran Duc Minh, Dang; Ba Huy, Dao; Huu Minh Quan, Le; Thi Tinh, Nguyen (VNU Journal of Science: Earth and Environmental Sciences, 2023)
Observed discharge time series is essential data for hydrological analysis, streamflow forecasting, as well as water resources planning and management. Estimation of continuous discharge time series is generally based on the curves (or empirical models) that can properly simulate the relationships between water levels (stages) and concurrent water discharges observed at a particular hydrological station. For stations with complex hydraulic conditions, in addition to gauged stages at the discharge gauging section, another variable such as stage measured at an auxiliary station (to calculate the slope) or rate of change in stage is added to the estimation process. This paper presents the results of applying the first-kind Chebyshev polynomial approximation method in constructing rating curves for three hydrological stations in the Da river basin, each having different basin characteristics and various influencing factors. The analysis results using five evaluation indices (MAE, σ, Pbias, KGE, and MAPE) show that the Chebyshev polynomials are highly effective in modelling both simple and complex stage-discharge relationships. The Chebyshev polynomial approximation method is suggested to be used for establishing stage-discharge relationships in hydrometry.